Implementasi Generative Artificial Intelligence sebagai Media Pembelajaran Adaptif untuk Meningkatkan Literasi Digital Mahasiswa Sistem Informasi - David Naista; Ghifar Javad H. Aziz; Singgih Yulizar Ma'ruf (PT. PENERBIT TIGA MUTIARA, 2026)
The development of Generative Artificial Intelligence (GenAI) has created new opportunities to develop more adaptive learning while enhancing students' digital literacy. This study aims to analyze the implementation of GenAI as an adaptive learning medium, its effect on improving digital literacy, and Information Systems students' perceptions of its use. This research employed a quantitative approach using a pre-experimental method with a one-group pre-test and post-test design. The results showed that the average digital literacy score increased from 68.8 to 85.0, representing an improvement of 16.2 points after the implementation of GenAI. The highest improvement was found in the Digital Safety and Ethics dimension with 19 points, followed by Digital Content Creation with 17 points, Information Literacy and Digital Technology Utilization with 16 points each, and Digital Communication and Collaboration with 13 points. The paired sample t-test produced a t-value of 8.45 with a significance level of 0.000, indicating that the implementation of GenAI had a statistically significant effect on improving students' digital literacy. The students also expressed positive perceptions of GenAI because it facilitated their understanding of learning materials, increased learning motivation, and supported more effective completion of academic tasks. This study concludes that GenAI is an effective adaptive learning medium for improving students' digital literacy. The novelty of this study lies in the development of a GenAI implementation model that integrates adaptive learning with the five dimensions of digital literacy among Information Systems students in a comprehensive manner.